Liposomes for the Treatment of Brain Cancer-A Review - Richu Raju; Waad H. Abuwatfa; William G. Pitt; Ghaleb A. Husseini (MDPI AG, 2023)
Due to their biocompatibility, non-toxicity, and surface-conjugation capabilities, liposomes are effective nanocarriers that can encapsulate chemotherapeutic drugs and facilitate targeted delivery across the blood-brain barrier (BBB). Additionally, strategies have been explored to synthesize liposomes that respond to internal and/or external stimuli to release their payload controllably. Although research into liposomes for brain cancer treatment is still in its infancy, these systems have great potential to fundamentally change the drug delivery landscape. This review paper attempts to consolidate relevant literature regarding the delivery to the brain using nanocarriers, particularly liposomes. The paper first briefly explains conventional treatment modalities for cancer, followed by describing the blood-brain barrier and ways, challenges, and techniques involved in transporting drugs across the BBB. Various nanocarrier systems are introduced, with attention to liposomes, due to their ability to circumvent the challenges imposed by the BBB. Relevant studies involving liposomal systems researched to treat brain tumors are reviewed in vitro, in vivo, and clinical studies. Finally, the challenges associated with the use of liposomes to treat brain tumors and how they can be addressed are presented.